2016
DOI: 10.1161/hypertensionaha.116.07293
|View full text |Cite
|
Sign up to set email alerts
|

Unsupervised Placental Gene Expression Profiling Identifies Clinically Relevant Subclasses of Human Preeclampsia

Abstract: P reeclampsia (PE) is a potentially life-threatening, systemic, hypertensive disorder affecting 3% to 5% of all pregnancies. Responsible for >60 000 maternal deaths each year, 1 PE is also a leading cause of fetal/neonatal mortality and morbidity. Classically, PE has been defined as new-onset hypertension and proteinuria after 20 weeks of gestation. However, the clinical presentation of PE is highly variable among women, and diagnostic guidelines now include signs and symptoms that are reflective of disease in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
256
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(283 citation statements)
references
References 50 publications
(49 reference statements)
16
256
0
Order By: Relevance
“…Leavey et al 39 found specific correlations with microarray data (from large cohorts of preeclamptic placentas) with clinical findings and propose subclasses of preeclampsia distinct to the canonical disease (which is driven by antiangiogenic factors). They identified a cluster of patients they coined immunologic preeclampsia where the main drivers of the disease may be immunologic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Leavey et al 39 found specific correlations with microarray data (from large cohorts of preeclamptic placentas) with clinical findings and propose subclasses of preeclampsia distinct to the canonical disease (which is driven by antiangiogenic factors). They identified a cluster of patients they coined immunologic preeclampsia where the main drivers of the disease may be immunologic.…”
Section: Discussionmentioning
confidence: 99%
“…They identified a cluster of patients they coined immunologic preeclampsia where the main drivers of the disease may be immunologic. 39 It is therefore possible that PPIs might be less effective for subtypes of preeclampsia where antiangiogenic factors play less of a role. As the field of preeclampsia subtyping matures, it may be feasible to stratify response to PPIs treatment in future clinical trials with preeclampsia subtyping.…”
Section: Discussionmentioning
confidence: 99%
“…It is also important to note that, although preeclampsia can be predicted with reasonable accuracy, it is a heterogeneous disease, and the relative contributions of risk factors are not known. 35 Additionally, the effects of LMWH on maternal cardiovascular was assessed for an acute time period after one administration of the agent; further longitudinal studies are thus warranted to evaluate whether the acute treatment effects demonstrated are maintained for a longer period of time.…”
Section: Perspectivesmentioning
confidence: 99%
“…10 In addition to morphologic and targeted molecular analyses, investigators are also applying global transcriptional profiling approaches to better understand the placental defects that are associated with preeclampsia. To date, these studies have focused on chorionic villi, 11,12 the maternal-fetal interface, 13 or purified cytotrophoblasts as they differentiate along the invasive pathway in vitro. 14 These studies have the advantage of being unbiased therefore enabling the de novo discovery of misregulated genes.…”
mentioning
confidence: 99%